Learning and/or “Cure”? The notion of learning context in the health ambit - Lahitte, Hector Blas (2020)
Mental health is not the object of study of only one discipline, but of different fields of knowledge including anthropology. If it is considered that (1) mental illness is related to learning and (2) learning happens in a relational context between the subject and his/her environment, it is possible to assume that a change in the context could mean changes in the subject’s health. Therefore, an approximation to the concept of “cure” may include the idea of building and reforming a habit of thought. By modifying a habit of thought, the individual can change their situation and improve their relationships with the environment, which tends to re-equilibration and health. In this work, this hypothesis is developed and empirical evidence was shown with five Wernicke Korsakoff’s Syndrome inpatients learning to solve the Tower of Hanoi that supports the assumptions. Conversely to what is expected to amnesic people, empirical results showed that the participants not only learned the task (proto-learning) but also improved their execution with practise and training (deutero-learning) and reached some level of flexibility. It is suggested that this behavioural change depends, at least in part, on the context created in the examiner-participant relationship. People are not ill per se but they are ill only in relation to an environment which surrounds and conditions them.